Silibus Kursus Mustalah Al-Hadis: Kajian Perbandingan Terhadap Penerimaan Pelajar di Institut Pengajian Tinggi (IPT) Islam - Ahmad, Khalilullah Amin; Mat Sin, Muhammad Lukman; Abdul Hamid, Solahuddin; Abdul Rahman, Mohd Nizho; Abdul Halim, Amran (USIM, 2023)
Mustalah al-Hadis is one of the courses in the Core component of Islamic Studies program offered at the Public Higher Education Institutions (IPTA) or Private Higher Education Institutions (IPTS) in Malaysia. The exposure of basic sciences of hadith in this course is able to strengthen the understanding of the hadith of Prophet Muhammad SAW, which is significant as the second source of legislation in Islam. In order to ensure that the learning process goes more smoothly in line with the development of the 21st Century Learning (PAK-21) and as a response to the challenges of Industrial Revolution 4.0 in the educational aspect, the Mustalah al-Hadis course is also not left behind in the Malaysia’s flow of education. Therefore, this article aims to examine students’ acceptance of the Mustalah al- Hadith course syllabus offered at Islamic Higher Education Institutions in northern Malaysia, namely Kolej Universiti Islam Perlis (KUIPs), Universiti Islam Antarabangsa Sultan Abdul Halim Mua’dzam Shah (UniSHAMS) and Kolej Islam Teknologi Antarabangsa (KITAB), Pulau Pinang. This qualitative study takes the form of interviews, observations and document analysis involving lecturers and students taking the Mustalah al-Hadis course. The findings of the study can be concluded that the students’ acceptance of the Mustalah al-Hadis course syllabus depends on the educational background and the students’ determination to learn this course as well as the teaching methodology applied by the course lecturer